45,X/46,XX mosaicism in patients with idiopathic premature ovarian failure - Devi, Anne S.; Metzger, Deborah A.; Luciano, Anthony A.; Benn, Peter A. (Fertility and sterility, 1998)
Objective: To determine whether low-level 45,X/46,XX mosaicism may be present in some women with premature ovarian failure (POF). Design: Slide preparations were made from lymphocyte cultures stimulated with phytohemagglutinin, and fluorescence in situ hybridization (FISH) was then performed using a biotin-labeled X-chromosome probe. Setting: Cytogenetics laboratory. Patient(s): Fifteen women with idiopathic POF, 20 age-matched controls, and an additional 10 older control women with normal reproductive histories. Intervention(s): Blood samples were collected. Main Outcome Measure(s): The number of X chromosomes present in each cell. Result(s): In patients with POF, the percentage of cells with a single X chromosome (mean, 5.50) was significantly greater than in the controls of similar age (mean, 2.42). For control subjects, there appeared to be a linear correlation between the number of cells with a single X chromosome and age. Conclusion(s): Some cases of POF may be attributable to low-level 45,X/46,XX mosaicism, which can be detected using FISH. In the lymphocytes from normal women, the rate of accumulation of cells with a single X chromosome was approximately 700 per 10 6 cells per year.